2021
DOI: 10.1371/journal.pone.0252062
|View full text |Cite
|
Sign up to set email alerts
|

Conditional transparency: Differentiated news framings of COVID-19 severity in the pre-crisis stage in China

Abstract: Transparency of Chinese media coverage became an international controversy when the COVID-19 outbreak initially emerged in Wuhan, the eventual crisis epicenter in China. Unlike studies characterizing mass media in authoritarian contexts as government mouthpieces during a crisis, this study aims to disaggregate Chinese media practices to uncover differences in when, where, and how the severity of COVID-19 was reported. We examine differences in how media institutions reported the severity of the COVID-19 epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…If the quotient is greater than one, the model would violate the assumptions of the Poisson distribution. 82,83 Given our quotient is 1.45, it indicates that the residual deviance is greater by 45% and there exists an overdispersion problem. Hence, multilevel regression models with negative binomial distributions were adopted for data analysis in this study.…”
Section: Discussionmentioning
confidence: 96%
“…If the quotient is greater than one, the model would violate the assumptions of the Poisson distribution. 82,83 Given our quotient is 1.45, it indicates that the residual deviance is greater by 45% and there exists an overdispersion problem. Hence, multilevel regression models with negative binomial distributions were adopted for data analysis in this study.…”
Section: Discussionmentioning
confidence: 96%
“…The main coding category involved news frames. This study preliminarily identified five news frames and their operational definitions in existing theoretical and empirical studies [ 73 , 74 ]: the reassurance, attribution of responsibility, governance, panic, and science frames. We also introduced two new frames not defined by existing theories or studies: the endemic frame and the sexual transmission frame.…”
Section: Methodsmentioning
confidence: 99%
“…However, semi-privatized commercial media do publish original content by offering additional information as an alternative to official propaganda (for details of semi-privatized commercial media in China, see [ 26 ]). For example, some semi-privatized commercial media like Sina covered stories that addressed the severity of the COVID-19 pandemic during the prepandemic period between January 1 and 20, 2020 [ 27 ]. As a result, both Chinese official media (e.g., People's Daily, Xinhua News Agency, and CCTV) and semi-privatized commercial media (e.g., Caixin and Sanlian Life Weekly) news articles on social media platforms have played a role in covering the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%